Direct and indirect costs of patients from Medan who seek health care in Penang Malaysia (Berita Kedokteran Masyarakat (BKM), 2020)
Background. Medan City was one of the areas close to Malaysia. This closeness makes people visit Penang Island for many reason such as medician, or medical tourism, with an increase 15-18% every year. This medical tourism causes people to spend more cost, both direct and indirect cost, direct costs were related to medician cost, (doctor's fees, medicines, laboratories, administration, and medical support), while indirect costs were unrelated with medician cost, (transportation, residence, supplementary food, patient companion, and lost costs). Purpose. The purpose of study was to analyze the comparison of direct and indirect costs of medical tourism patients to Penang Island, Malaysia. Method. This research was a comparative analytic with cross-sectional design using a questionnaire, conducted with t test for comparison of direct and indirect costs for 96 respondents. Result. The results showed that the expenditure average of medical tourism patient was IDR 10,079,250, with comparison of direct and indirect costs was 55.8%: 44.2% or IDR 5,625,305: IDR 4,453,945. Conclusion. Government makes regulations related to seeking medician abroad, and improve the quality of domestic health services so expenditure for medical treatment abroad can saved.